Caregivers’ knowledge on epilepsy and its relationship with quality of life - Lee, Khuan; Hamzah, Nurul Nadhirah; Abdul Rashid, Nor'ain (2023)
.It is widely accepted that epilepsy is a disease that affects not only patients but also their families. The disease has a relevant impact on caregivers’ quality of life. The study aimed to determine caregivers’ knowledge of epilepsy and its relationship with their quality of life. Total of 308 participants were recruited. The Awareness Knowledge Attitude Questionnaire and the Adult Carer – Quality of Life (AC-QoL) questionnaire were used. The result demonstrates a significant association between caregivers’ knowledge levels and the level of their quality of life. A significant association was identified between two socio-demographic characteristics - marital status and educational level - and level of knowledge. Furthermore, significant associations were found between other socio-demographic characteristics and the level of their quality of life: religion, marital status, educational level and monthly income. The findings of the study indicate that caregivers with high levels of epilepsy-related knowledge experience a moderate quality of life. Therefore, epilepsy support groups for caregivers are important as these would provide the appropriate emotional and practical support needed to improve the quality of live among caregivers